PENGARUH TINGKAT PENDIDIKAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA - Henni Lastri; Andi Warisno; Muhammad Afif Anshori; Sulthan Syahril (UNISAN JURNAL, 2022)
This study aims to determine the effect of parents' educational level on students' learning motivation at MTs Di'ayatul Islamiyah Seriguna. To collect data relevant to this research, used the Questionnaire method, Documentation Method, Observation Method, Interview Method. After the data is well collected, the next step is to process or analyze the data to prove or test the hypotheses that have been formulated, while the analytical method used in this study is Percentage, Chi Square analysis method. The results of research on the effect of parents' education level on the learning motivation of MTs Di'ayatul Islamiyah Seriguna students, the authors conclude that there is an influence between the level of parental education and the learning motivation of MTs Di'ayatul Islamiyah Seriguna students because the interpretation value is very strong, namely 22.084.